203k views
5 votes
Look at the screenshots for the answers. (50 points)

Look at the screenshots for the answers. (50 points)-example-1
Look at the screenshots for the answers. (50 points)-example-1
Look at the screenshots for the answers. (50 points)-example-2
Look at the screenshots for the answers. (50 points)-example-3
Look at the screenshots for the answers. (50 points)-example-4
Look at the screenshots for the answers. (50 points)-example-5
User Mon Io
by
5.8k points

2 Answers

5 votes

Answer:

bbbbbbbbbbbbbb

Explanation:

User Dave Lee
by
5.2k points
3 votes

(1)

we are given


f(x)=5x^2-2x


g(x)=3x^2+x-4


(f+g)(x)=f(x)+g(x)

now, we can plug


(f+g)(x)=5x^2-2x+3x^2+x-4


(f+g)(x)=8x^2-x-4...........Answer

(2)

we are given


f(x)=2x^2-3


g(x)=x+4


(fg)(x)=f(x) * g(x)

now, we can plug


(fg)(x)=(2x^2-3) * (x+4)


(fg)(x)=2x^3+8x^2-3x-12...........Answer

(3)

we are given


f(x)=3x^2+10x-8


g(x)=3x^2-2x

we have


((f)/(g) )(x)=(f(x))/(g(x))

now, we can plug values


((f)/(g) )(x)=(3x^2+10x-8)/(3x^2 -2x)

now, we can factor it


((f)/(g) )(x)=((3x-2)(x+4))/(x(3x -2))

now, we can factor it


((f)/(g) )(x)=((x+4))/(x)

we know that denominator can not be zero

so,


3x^2-2x\\eq 0


x\\eq 0, x\\eq (2/3)

so, option-C.........Answer

(4)

we are given


r(x)=x^2+6x+10


c(x)=x^2-4x+5


(r-c)(x)=r(x)-c(x)

now, we can plug it


(r-c)(x)=x^2+6x+10-(x^2-4x+5)


(r-c)(x)=10x+5

now, we can plug x=4


(r-c)(4)=10*4+5


(r-c)(4)=45

so, option-C..................Answer

(5)

we are given


c(x)=50+5x


p(x)=100-2x


(p*c)(x)=p(x)*c(x)

now, we can plug values


(p*c)(x)=(50+5x)*(100-2x)

now, we can plug x=2


(p*c)(2)=(50+5*2)*(100-2*2)


(p*c)(2)=5760

we know that

price is


c(x)=50+5x

we can plug x=2


c(2)=50+5*2


c(2)=60

so, option-B...............Answer

User Symara
by
5.5k points